Hidden blood loss and risk factors after percutaneous endoscopic transforaminal lumbar interbody fusion - Ge, Meng; Zhu, Fangbing; Du, Weibin; Ye, Zhengcong; Xiong, Zhenfei; Zhang, Lukai; Zhou, Hua; Yang, Jun (Frontiers in Surgery, 2025)
PurposeIn this study, we aimed to assess the occurrence of hidden blood loss (HBL) and its associated risk factors in patients with lumbar degenerative diseases who underwent percutaneous endoscopic transforaminal lumbar interbody fusion (Endo-TLIF).MethodsSex, age, height, weight, body mass index, and medical history including hypertension, diabetes, and osteoporosis were recorded. The duration of symptoms, preoperative lumbar subcutaneous fat tissue thickness (measured using midsagittal T2-weighted magnetic resonance imaging), lumbar disc degeneration grade, and other basic patient information were also documented. The levels of fibrinogen, activated partial thromboplastin time, prothrombin time, thrombin time, and platelet count as well as the pre- and postoperative hematocrit and hemoglobin levels were collected. In addition, the number of fusion levels, surgical time, and intraoperative blood loss were recorded. Total blood loss (TBL) was calculated using the gross formula, and HBL was calculated based on the TBL and visible blood loss. The risk factors were analyzed using single-factor correlation and multivariate linear regression analyses.ResultsOf the 83 patients, there were 42 males and 41 females. Hypertension (P = 0.003), fusion level (P < 0.001), and surgery time (P < 0.001) were significantly correlated with HBL via a single-factor correlation analysis. Multiple linear regression analysis showed that the fusion level (P < 0.001) and surgery time (P < 0.001) were independent risk factors for HBL.ConclusionIn patients with lumbar degenerative diseases treated with Endo-TLIF, HBL accounts for a large proportion of TBL. A large number of fusion segments and prolonged operation time are risk factors for increased perioperative HBL during Endo-TLIF. Increased attention should be paid to the presence of HBL to ensure the safety of perioperative patients.